(untitled) (Italian Journal of Public Health, 2009)
Background: Primary care in the Netherlands has a strong international reputation. However, this picture may be qualified in two respects. First of all, the Dutch primary care system is less cohesive than is sometimes suggested. Secondly, there are major challenges in the Dutch system (as is the case with other European health care systems), which have to be resolved in order to maintain and improve primary care. Methods: Description of primary care in the Netherlands based on nationally and internationally published sources. Identification of challenges and trends. Narrative review of the literature. Results: GPs have a strong position in the Netherlands. Their numbers are relatively low; they have a gatekeeping position, and there is no cost-sharing for GP care (unlike other forms of care). The primary care system as a whole, however, is characterised by weak coherence. Individual primary care disciplines have their own separate modes of funding. Challenges include a growing and changing demand for primary care services, and changes in manpower and organisation, that affect the balance between demand and supply regarding primary care services. Conclusions: Among the threats to strong primary care are the risk of increasing fragmentation of care, negative side effects of a transformation process from cottage industry to service industry, and reluctance to invest in integrated primary care. An opportunity lies in the consensus among stakeholders that integrated primary care has a future. Technological developments support this, especially the development of electronic patient records.